2007
DOI: 10.1111/j.1365-3024.2007.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immune responses in mice infected with different strains of Strongyloides venezuelensis

Abstract: In human hosts and in murine models, the immune response to Strongyloides spp. is Th2 type. In addition, the profile of the host immune response follows various symptoms induced by Strongyloides spp. In the present study, we demonstrated that the L2 and L49 strains of Strongyloides venezuelensis obtained from Bolomys lasiurus and Nectomys squamipes induced significant and similar increases in eosinophil/mononuclear cell counts in the blood, peritoneal cavity fluid and bronchoalveolar lavage fluid when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
4
12
0
3
Order By: Relevance
“…This tendency became evident at the recovery phase when IgG1 but not IgG2b presented a significant increase compared with that in the acute infection. These results are similar to the ones described in mice infected with S. venezuelensis (3) and Wistar rats infected with S. ratti (5). Wilkes et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This tendency became evident at the recovery phase when IgG1 but not IgG2b presented a significant increase compared with that in the acute infection. These results are similar to the ones described in mice infected with S. venezuelensis (3) and Wistar rats infected with S. ratti (5). Wilkes et al.…”
Section: Discussionsupporting
confidence: 90%
“…However, different kinds of immune response can be observed with different strains of Strongyloides spp. Recently, a study comparing two heterologous strains of S. venezuelensis showed that the strains differed in the stimulation of humoral immune response (3). The dynamics of S. venezuelensis infection, especially concerning the kinetics of egg elimination, the induced immunity and the tissue migration route, are already known in Wistar rats (8,9) and in several mice strains (10), but not in Lewis rats.…”
Section: Introductionmentioning
confidence: 99%
“…Mice have been provided with immunity by transferring human IgG [22]. Moreover, L2 strains could have more potent stimulus of humoral response than L3 in mice [23]. Interestingly, in some nematodes, the Th1 response is elucidated with low intensity of infection, whereas Th2 is induced with high doses of worms [24].…”
Section: Overview Of the Pathogenesis And Immune Response Of Strongylmentioning
confidence: 98%
“…In immunocompromised patients with excess parasites the disease may become potentially fatal due to hyperinfection syndrome and dissemination, besides being related to the highest mortality rate (Grove, 1996). However, there has been little investigation into the causes of this disease presentation form and the worst outcome (Machado et al, 2007).…”
Section: Introductionmentioning
confidence: 99%